2002
DOI: 10.1046/j.1464-410x.2002.02734.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparative dose‐ranging study of interferon‐α and mitomycin‐C as an internal control in primary or recurrent superficial transitional cell carcinoma of the bladder

Abstract: Ablative therapy with interferon-alpha was less effective than mitomycin-C in patients with superficial bladder cancer. Both drugs were well tolerated, although interferon-alpha appeared to have a slightly better overall safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 20 publications
(19 reference statements)
0
5
0
3
Order By: Relevance
“…Unfortunately, although intravesical chemotherapy decreases tumor recurrence rate in the short-term (1-2 years), long-term results are disappointing, indicating that the proportion of patients having recurrent tumor at ≥5 years is the same or even higher than for those treated by TUR alone [12,13]. Moreover, recent publications reported that perioperative single-dose instillation of epirubicin or weekly administration of mitomycin were more effective in prevention of primary TCC recurrence than IFNa2b treatment [16,17]. After the favorable report of Morales et al [14] in 1976, BCG has been used as a prophylactic and therapeutic agent, introducing immunotherapy in the management of TCC.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, although intravesical chemotherapy decreases tumor recurrence rate in the short-term (1-2 years), long-term results are disappointing, indicating that the proportion of patients having recurrent tumor at ≥5 years is the same or even higher than for those treated by TUR alone [12,13]. Moreover, recent publications reported that perioperative single-dose instillation of epirubicin or weekly administration of mitomycin were more effective in prevention of primary TCC recurrence than IFNa2b treatment [16,17]. After the favorable report of Morales et al [14] in 1976, BCG has been used as a prophylactic and therapeutic agent, introducing immunotherapy in the management of TCC.…”
Section: Discussionmentioning
confidence: 99%
“…Interferon- α (IFN- α ) is a pleiotropic immune modulator that has demonstrated antiproliferative activity in several preclinical studies. While the results of interferon- α 2 β (IFN- α 2 β ) as intravesical monotherapy has proven to be inferior to standard therapies [ 9 ], in vitro studies have shown that the addition of IFN- α 2 β to BCG potentiates the TH1-type response [ 10 ]. O'Donnell and colleagues proposed the addition of IFN- α 2 β to a BCG regimen with the hope it would synergistically elicit an appropriate host response in patients who have failed induction BCG therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Παρουσιάζει τη µέγιστη δραστικότητά της όταν χορηγείται ενδοκυστικά και λιγότερο υπό µορφή ενδο-ογκικής έγχυσης, που πρακτικά έχει εγκαταλειφθεί. Το ιδανικό δοσολογικό σχήµα δεν έχει ακόµη καθοριστεί, αλλά σε γενικές γραµµές χορηγούνται δόσεις που κυµαίνονται µεταξύ 40 έως 100 εκατοµµυρίων διεθνών µονάδων 251,252 .…”
Section: β σκευάσµατα και χορήγησηunclassified
“…Ιστορικά, η πρώτη ενδοκυστική χορήγηση ιντερφερόνης-α (λεµφοβλαστοειδούς προέλευσης) σε επιφανειακό καρκίνο της ουροδόχου κύστης πραγµατοποιήθηκε το 1986 από τον Oliver και συν 259 . Το ιδανικό δοσολογικό σχήµα, υπό την έννοια του βέλτιστου συνδυασµού δόσης και συχνότητας χορήγησης, δεν έχει ακόµη καθοριστεί 251 .…”
Section: γ θεραπευτικές εφαρµογές στον καρκίνο της ουροδόχου κύστηςunclassified
See 1 more Smart Citation